Photovoice as a research, advocacy, and harmonization tool for refugee and local youth in Turkey. (20th October 2021) - Karadag Caman, O; Ceyhan, DI; Sumbuloglu, I; Karabey, S; Ben Amor, Y
Abstract: Background: Turkey has millions of refugee and local youth, who share common youth health problems. As part of the REACH Project, this study aimed to assess youth's access to health information, health care, and healthy environments, in addition to their perspectives on using digital health technologies. Methods: We used photovoice, a community based participatory research approach, and worked with 4 mixed (refugee and local) youth groups between the ages of 15 to 24 in Istanbul. Each youth group met with the research team and a professional photographer before data collection. Young people then took photos of barriers and facilitators regarding their access to health information, health care, and digital health technologies, in addition to their health problems. This was followed by focus group-like discussions, where young people discussed the photos and their meanings for them. Content analysis was used for data analysis and findings were shared with stakeholders via photo exhibits, panels, and policy briefs for advocacy purposes. The study was funded by TaiwanICDF and Columbia University. Results: Findings showed that youth had a wide range of physical, social and mental health problems coupled with problems in accessing health information and youth-friendly services. Problems with social determinants of health were more prominent for refugees. Although youth often used the internet to access information, their experiences with digital health technologies were very limited. Conclusions: Our study findings indicated that despite legal rights to access health care for all youth, refugee youth faced more barriers in accessing information and services. On the other hand, refugee and local youth showed similarities regarding common youth health problems and access to youth-friendly services. The photovoice approach enabled active participation and created a shared environment for refugee and local youth to discuss their mutual problems and understand each other. Key messages: Photography is a communication tool that acts as a bridge between participants, researchers, and decision makers. Photovoice, as a participatory approach, creates a learning environment for both participants and researchers.